2011
DOI: 10.1007/s10623-011-9562-5
|View full text |Cite
|
Sign up to set email alerts
|

Projective k-arcs and 2-level secret-sharing schemes

Abstract: Motivated by applications to 2-level secret sharing schemes, we investigate k-arcs contained in a (q + 1)-arc of PG(3, q), q even, which have only a small number of focuses on a real axis of . Doing so, we also investigate hyperfocused and sharply focused arcs contained in a translation oval of PG(2, q).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Cherowitzo and Holder [4] classified all hyperfocused arcs contained in a regular hyperoval. In [14] showed that this classification extends to every translation hyperoval Ω provided that ℓ is the special chord of Ω. Faina and Pasticci [6] proved that in small planes and for special values of k, every hyperfocused k-arc is contained in a regular hyperoval. Nevertheless, Giulietti and Montanucci [9] constructed a family of hyperfocused arcs not contained in any hyperoval.…”
Section: Hyperfocused Arcs In P G(2 Q)mentioning
confidence: 96%
“…Cherowitzo and Holder [4] classified all hyperfocused arcs contained in a regular hyperoval. In [14] showed that this classification extends to every translation hyperoval Ω provided that ℓ is the special chord of Ω. Faina and Pasticci [6] proved that in small planes and for special values of k, every hyperfocused k-arc is contained in a regular hyperoval. Nevertheless, Giulietti and Montanucci [9] constructed a family of hyperfocused arcs not contained in any hyperoval.…”
Section: Hyperfocused Arcs In P G(2 Q)mentioning
confidence: 96%
“…Of course the two words in italics need to be given a precise meaning. A very special case of this occurred in [KLS12,Lemma 5.3], where the conclusion was proved under the assumption that A is inverse closed up to at most two nonzero elements.…”
Section: Introductionmentioning
confidence: 98%
“…codes and k-arcs are equivalent objects; see [16]. For more on the connection between arcs and secret sharing schemes, see, for instance, [9], [10], and [14]. For these reasons, in recent years there has been great interest in constructing new arcs in projective spaces; see [2], [7], [8], [11], [12], [13], [15].…”
Section: Introductionmentioning
confidence: 99%